Towards Successful Deployment of Wellbeing Sensing Technologies: Identifying Misalignments across Contextual Boundaries - Suh, Jina; Hernandez, Javier; Saha, Koustuv; Dixon, Kathy; Bin Morshed, Mehrab; Howe, Esther; Kawakami, Anna; Czerwinski, Mary (ACII 2023 International Workshop on Affective Computing for Mental Wellbeing, 2023)
Affective computing technologies have emerged as promising tools for supporting mental health and wellbeing but face deployment challenges in work and nonwork contexts due to misalignments in boundary preferences, data ownership, values and incentives, wellbeing definitions, and power dynamics. This paper presents a case study on the deployment of a just-in-time emotional support agent in the workplace, highlighting the five categories of misalignments that undermine the successful deployment of personal mental health support systems across these contextual boundaries. The identification and analysis of these misalignments contributes to a deeper understanding of the complexities and challenges faced when implementing affective computing systems for holistic mental health support. By emphasizing the importance of considering these misalignments in future research and development, this paper aims to contribute to the ongoing discourse on the effective and ethical deployment of affective computing technologies across work and nonwork contexts.